Can we use case method for all pre-service teachers? : The influence of pre-service teacher’s characteristics on case learning - Liu, Wei-Yu (Advances in Social Sciences Research Journal, 2019)
This study is to explore the influence of student characteristics on case learning. How do the influence of gender, experience, major and learning style on pre-service teachers’ case learning? There are thirty-seven preservice teachers in the Elementary Education Program of Center for Teacher Education at National Dong-Hwa University in Taiwan participated in this study. The results show that there is difference between pre case discussion decision making and post case discussion decision making and decision making perspectives. There is no difference in the influence of pre-service teachers’ gender, teaching experience, and learning styles on case learning. That is, case method is effective for all preservice teachers, no matter what characteristics are they. However, all learning styles except for assimilating learning style have more pre-service teachers changed than no changed. Does it indicate that assimilating learning style pre-service teachers might have difficulty to learn from case method because they in favor of abstract concepts instead of real case? More researches are needed for understanding the influence of pre-service teachers’ learning style on case learning.